2022
DOI: 10.1088/1751-8121/ac9261
|View full text |Cite
|
Sign up to set email alerts
|

Resetting photons

Abstract: Starting from a frequency diffusion process for a tagged photon which simulates relaxation to the Planck law, we introduce a resetting where photons lower their frequency at random times. We consider two versions, one where the resetting to low frequency is independent of the existing frequency and a second case where the reduction in frequency scales with the original frequency. The result is a nonlinear Markov process where the stationary distribution modifies the Planck law by abundance of low-frequency occup… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Let us finish by emphasizing that the proposed mechanisms remain conjectural and that the theory is largely phenomenological. A follow-up can be found in [56], where a resetting mechanism is added to the Kompaneets process corresponding to random abrupt Doppler shifts to the low frequency regime.…”
Section: A Adding Low-frequency Diffusionmentioning
confidence: 99%
“…Let us finish by emphasizing that the proposed mechanisms remain conjectural and that the theory is largely phenomenological. A follow-up can be found in [56], where a resetting mechanism is added to the Kompaneets process corresponding to random abrupt Doppler shifts to the low frequency regime.…”
Section: A Adding Low-frequency Diffusionmentioning
confidence: 99%
“…Oliveira et al have investigated how would the black body radiation curve get modified if the photon frequencies are subject to resetting [76]. They found that the effect of frequency resetting on the radiation curve gets manifested by abundance of low-frequency occupation.…”
mentioning
confidence: 99%